Repensando as interpretações e memórias de 1968 - Almada, Pablo Emanuel Romero [UNESP] (Departamento de Sociologia da Faculdade de Filosofia, Letras e Ciências Humanas da Universidade de São Paulo, 2021)
The article analyzes how the interpretations and memories of the events of 1968 are transformed during their decimal celebrations. It is based on the qualitative analysis of the History of the Present Time, addressing the Memory Policies around the meanings that those events have gained over its 50 years, both by its interpreters and by the protagonists. It is argued that the wide range of studies valued their subjects and conflicts, opening a huge range of interpretations, which guide 1968 through the present time, renewing their memories. It concludes by discussing memorialist lines on collective actors and new reports by protagonists, which allow reinterpretations of 1968, in its fifties, explaining its dialogue with current political identities.

O artigo analisa como as interpretações e as memórias dos acontecimentos de 1968 se transformam ao longo de suas comemorações decimais. Respalda-se na análise qualitativa da História do Tempo Presente, abordando as Políticas de Memória em torno dos sentidos que aqueles eventos foram ganhando ao longo de seus cinquenta anos, tanto por parte de seus intérpretes quanto pelos protagonistas. Argumenta-se que a ampla gama de estudos valorizou seus sujeitos e conflitos, abrindo um enorme leque de interpretações, as quais guiam 1968 pelo tempo presente, renovando as suas memórias. Conclui-se discutindo algumas linhas memorialísticas em torno dos atores coletivos e de novos relatos de protagonistas, que permitem reinterpretações de 1968, em seus cinquenta anos, elucidando o seu diálogo com as atuais identidades políticas.
Rethinking the interpretations and memories of 1968
Keywords: 1968; Students Movement; Resistance; Politics of Memory; Political identities; 1968; Movimento estudantil; Resistência; Políticas de Memória; Identidades políticas